Kajian Review Resistensi Escherichia coli Terhadap Antibiotik Β-Laktam Dan Aminoglikosida Pada Ternak Ayam Dan Produk Olahannya Di Indonesia - Elise M Ballo; Novalino Kallau; Nemay A Ndaong (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Antibiotic resistance is a problem of animal health and public health. Antibiotics used in the livestock industry generally aim to treat livestock to reduce the risk of death and restore the health condition of the livestock. However, the use of antibiotics in animals that are not as recommended and not according to the prescribed dose can increase the emergence of resistance. The aim of this literature study is to see the level of antibiotic resistance of the β-lactam and aminoglycosides against Escherichia coli in poultry in Indonesia. This research is a type of literature research related to the resistance of Escherichia coli to β-lactam and aminoglycoside antibiotics in poultry and their processed products. The data used comes from articles, scientific journals and ebooks sourced from Google Scholar with the help of Mendeley application for reference arrangement. Based on the results of the study, it is known that the Escherichia coli isolates found in chicken farms and animal-derived food from chicken farms have experienced a fairly high resistance with the range of Escherichia coli resistance in chicken farms to B-lactam antibiotics starting from 21.7%. to 100% with an average prevalence of 60.85% and the aminoglycoside class of antibiotics ranging from 12.5% to 100% with an average prevalence of 56.25%. While the percentage of Escherichia coli resistance in animal products to B-lactam antibiotics ranges from 12% to 100% with an average prevalence of 56% and the aminoglycoside class of antibiotics ranges from 10.5% to 100% with an average prevalence of 55.25%, it is also known that the incidence of resistance shows a high number in West Java and Bali which is supported by resistance data based on the sampling location.